Determinan Kepatuhan Generasi Milenial di Kota Tangerang Selatan dalam Menunaikan Zakat Profesi - Alifia Aulia Putri; Indri Yuliafitri (Journal of Islamic Economics and Finance, 2025)
Professional zakat has the largest collection potential in Indonesia, but there is still a gap in the realization of zakat collection. The presence of zakat, including professional zakat, can help alleviate poverty. South Tangerang City, with a majority Muslim population, has a high potential for zakat, but the poverty rate is still increasing every year. This study aims to analyze the factors that influence the compliance of Muslim millennials in South Tangerang City in paying professional zakat. The data collection technique used was a purposive sampling with a sample size of 150 people. The analysis method used is Partial Least Square Structural Equation Model (PLS-SEM) using SmartPLS 4 software. The results show that income, altruism, and religiosity have a significant effect on compliance in paying professional zakat, while zakat knowledge does not show a significant effect. This study concludes that knowledge of zakat is not enough to encourage a Muslim to fulfill the obligation to pay zakat because other factors, such as income, altruism, and religiosity, have a greater influence.